2011
DOI: 10.1097/qai.0b013e318204194c
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual Behaviors of Adolescent Emerging and Young Adult Men Who Have Sex With Men Ages 13–29 in New York City

Abstract: Black and Latino YMSM may be at increased risk for seroconversion because they tend to start having sex with other men at a younger age than their white and Asian/Pacific Islander peers and because they engage in unprotected sexual behaviors with men of concordant race/ethnicity and of a similar age where levels of viremia may be more elevated but not because of the sheer number of sexual partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 13 publications
0
39
0
1
Order By: Relevance
“…For Phase 1, participants aged 18 to 29 (N = 540) were recruited using active methods over 90 days during the summer of 2008 for completion of a quantitative survey using tacit consent (see Halkitis, Brockwell, Moeller, Siconolfi, Cutler, & Sussman, 2011). Upon completion of the survey, participants were provided a $10 incentive and a palm card to contact the research center to take part in the interview.…”
Section: Methods Study Design and Proceduresmentioning
confidence: 99%
“…For Phase 1, participants aged 18 to 29 (N = 540) were recruited using active methods over 90 days during the summer of 2008 for completion of a quantitative survey using tacit consent (see Halkitis, Brockwell, Moeller, Siconolfi, Cutler, & Sussman, 2011). Upon completion of the survey, participants were provided a $10 incentive and a palm card to contact the research center to take part in the interview.…”
Section: Methods Study Design and Proceduresmentioning
confidence: 99%
“…Researchers mostly provided descriptive statistics around participants having receptive or insertive anal sex, with some studies noting differences across racial/ethnic groups. In one study, researchers reported that Latino participants were significantly more likely to have engaged in receptive anal sex when compared with Black participants; in another, researchers noted that Black participants were more likely than White participants to have engaged in receptive anal sex in their most recent sexual encounter with a causal partner (Halkitis et al, 2011;Warren et al, 2007). The distinction between casual versus primary partners (i.e., relationship type) was also frequently referenced across articles, with a wide range of unique findings.…”
Section: Discussionmentioning
confidence: 99%
“…Participants ages 18-29 (N=540) were recruited using active methods over 90 days during the summer of 2008 for completion of a quantitative survey using tacit consent (see Halkitis et al). 44 Research staff employed targeted sampling procedures at various venues throughout the five boroughs of NYC, including several large community events, social venues, bars, dance clubs, and public spaces (parks, street corners, etc.). The sampling frame was stratified so that Black and Latino men accounted for at least two thirds of the sample, and so that 33% percent of the sample was between the ages of each 18-20, 21-25, and 26-29, respectively.…”
Section: Procedures and Participantsmentioning
confidence: 99%